Testing Structural Hypotheses on Cointegration Vectors: A Monte Carlo Study - Åsa Eriksson (Lund University, School of Economics and Management, Department of Economics, 2004)
In this paper, two tests for structural hypotheses on cointegration vectors are evaluated in a Monte Carlo study. The tests are the likelihood ratio test proposed by Johansen (1991) and the test for stationarity proposed by Kwiatkowski et al (1992). The analysis of the likelihood ratio test is extended with the inclusion of a Bartlett correction factor. Under circumstances common in empirical applications, all tests suffer from large size distortions and have low power to detect a false cointegration vector, but the Johansen (1991) test fares slightly better than the Kwiatkowski et al (1992) test. Applying a Bartlett correction factor in small samples improves to a large extent the likelihood ratio test.
Keywords: C12; C15; C22; 330; Cointegration; Structural hypothesis; Monte Carlo simulation